Energetics of Defects on Graphene through Fluorination. Issue 5 (12th February 2014) - Xiao, Jie; Meduri, Praveen; Chen, Honghao; Wang, Zhiguo; Gao, Fei; Hu, Jianzhi; Feng, Ju; Hu, Mary; Dai, Sheng; Brown, Suree; Adcock, Jamie L.; Deng, Zhiqun; et al.
Abstract Functionalized graphene sheets (FGSs) comprise a unique member of the carbon family, demonstrating excellent electrical conductivity and mechanical strength. However, the detailed chemical composition of this material is still unclear. Herein, we take advantage of the fluorination process to semiquantitatively probe the defects and functional groups on graphene surface. Functionalized graphene sheets are used as substrate for low‐temperature (<150 °C) direct fluorination. The fluorine content has been modified to investigate the formation mechanism of different functional groups such as CF, CF2, OCF2 and (CO)F during fluorination. The detailed structure and chemical bonds are simulated by density functional theory (DFT) and quantified experimentally by nuclear magnetic resonance (NMR). The electrochemical properties of fluorinated graphene are also discussed extending the use of graphene from fundamental research to practical applications.